Atalanta i Hippomenes, czy Rozamunda i Abibas? - Szostek, Teresa (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The story of the contest of Atalanta and Hippomenes appears several times in ancient literature, and was also drawn on by medieval authors. The testimony to the creative use of this familar theme is that at least two verses mention the heroes’ struggles in the account known as Gesta Romanorum.
Keywords: Gesta Romanorum; literatura średniowieczna; mitologia; recepcja antyku; Atalanta; Hippomenes